Yellow forelock–a new neuro-ophthalmological sign. Issue 8 (August 1990) - Kellen, R. I.; Schrank, B.; Burde, R. M.
Abstract : We examined a middle-aged man with a prominent yellow forelock who complained of loss of vision in both eyes. He smoked his pipe avidly and drank a little Bourbon whisky daily. The nicotine content of the forelock (21.7 ng/mg) was 10 times that of the hair on his occiput (2.23 ng/mg). A yellow forelock when associated with isolated painless visual loss suggests tobacco amblyopia.